Os fundamentos de gestão do espaço urbano para a promoção da função socioambiental da cidade [manuscrito]: o caso de Goiânia - Martins Júnior, Osmar Pires (2013)
The studies in this paper are included in urban ambience marked by conflict paradoxical common sustainability of human actions and the evolutionary history of city planning in Latin America and Brazil in particular. The results are presented in accordance with this historical context, but in disagreement to what would be expected by the application of legally created instrumental in the City Statute – EC in 2001 as onerous grant and transfer the right to build. The results of case studies on Goiânia, compared to what was practiced before, since its first Master Plan in 1938, based on the Land Use Zoning, given the absence of effective parameters of sustainability, strengthen the environmental character of segregation capitalist city, evidenced by the drastic reduction of the remaining native vegetation and loss of biodiversity, the occupation of the surrounding local conservation units, exemplified in the case study of Parks Vaca Brava, the Buritis and the Zoological Park/Lago das Rosas and the dilapidation of public goods.The field survey, geoprocessing and analysis of information obtained demonstrate the impact on the Buffer Zone of Conservation Units ventures deployed more intensively after the enactment of EC/2001 without the financial contribution to the environment and the community. Residents prejudiced have appealed to the courts to impound the outrageous ventures Master Plan and the environmental function of the city. As a result of the research is proposed to complement the instrumental City Statute with new tools for urban policy, capable of promoting ownership and distribution of both the locational advantages of the benefits of urban land or plus value, such as the benefits associated with urban green areas through an integrated and participatory methodology for estimating the economics of natural resources and the environment, without neglecting the necessary urban-rural integration of the Metropolitan Region of Goiânia/Goiás.